The study of characteristics of a surface discharge on the barium titanate; Technical Physics Letters; Vol. 50, No. 8 - Stepanov A. V. Andrey Vladimirovich; Konusov F. V. Fedor Valerievich; Pavlov S. K. Sergey Konstantinovich; Tarbokov V. A. Vladislav Aleksandrovich; Serebrennikov M. A. Maksim Anatolevich (2024, 2024)
Title screen